m = n/(n-1)
Given m equals 3 and n equals 1 then m3n3 equals?m3n3 = m*3*n*3 = 3*3*1*3 = [ 27 ]
Let the integers be m and n.∴ By the condition given in the question,m + n - mn = 72∴ m + n - mn = 71 + 1∴ m + n - mn - 1 = 71∴ (m - 1)(1 - n) = 71∴ (m - 1)(1 - n) = 1 × 71 = 71 × 1 = (-1) × (-71) = (-71) × (-1)Case 1:m - 1 = 1 and 1 - n = 71∴ (m, n) = (2, -70)Case 2:m - 1 = 71 and 1 - n = 1∴ (m , n) = (72, 0)This case is inadmissible as m, n are non zero integers.Case 3:m - 1 = -1 and 1 - n = -71∴ (m , n) = (0, 72)This case is inadmissible as m, n are non zero integers.Case 4:m - 1 = -71 and 1 - n = -1∴ (m, n) = (-70, 2)But as the given expression is symmetric, therefore, (2, -70) and (-70, 2) cannot be considered two different pairs.∴ We get only one solution.
mn - 4m - 5n + 20 = m(n - 4) - 5(n - 4) = (n - 4)(m - 5)
m = 24
m = n/(n-1)
m(n + 1)
Given m equals 3 and n equals 1 then m3n3 equals?m3n3 = m*3*n*3 = 3*3*1*3 = [ 27 ]
If ( mn = 161 ), then ( m = \frac{161}{n} ). Without knowing the value of ( n ), it is not possible to determine the value of ( mm ).
m *n (m multiplied by n) would be mn.
Let the integers be m and n.∴ By the condition given in the question,m + n - mn = 72∴ m + n - mn = 71 + 1∴ m + n - mn - 1 = 71∴ (m - 1)(1 - n) = 71∴ (m - 1)(1 - n) = 1 × 71 = 71 × 1 = (-1) × (-71) = (-71) × (-1)Case 1:m - 1 = 1 and 1 - n = 71∴ (m, n) = (2, -70)Case 2:m - 1 = 71 and 1 - n = 1∴ (m , n) = (72, 0)This case is inadmissible as m, n are non zero integers.Case 3:m - 1 = -1 and 1 - n = -71∴ (m , n) = (0, 72)This case is inadmissible as m, n are non zero integers.Case 4:m - 1 = -71 and 1 - n = -1∴ (m, n) = (-70, 2)But as the given expression is symmetric, therefore, (2, -70) and (-70, 2) cannot be considered two different pairs.∴ We get only one solution.
mn - 15 + 3m - 5n Rearranging: mn + 3m - 5n - 15 = m(n + 3) - 5(n + 3) = (m - 5)*(n + 3)
mn - 4m - 5n + 20 = m(n - 4) - 5(n - 4) = (n - 4)(m - 5)
mn - 4m - 5n + 20 = (mn - 5n) - (4m - 20) = n(m - 5) - 4(m - 5) = (m -5)(n - 4)
Let m be a whole number, then the multiplicative inverse of m is a number n such that mn=1 since 1 is the multiplicative identity. There is only one choice for n, it is 1/m since m(1/m)=1
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. Some possibilities are: mn + mp + 3nq + 3pq = (m+3q)*(n+p) mn - mp - 3nq + 3pq = (m-3q)*(n-p) mn + mp - 3nq - 3pq = (m-3q)*(n+p) mn - mp + 3nq - 3pq = (m+3q)*(n-p) If your question is for something else, please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc.
m = xn/(n + y)